Resident Alien : On Border-crossing and the Undocumented Divine - Ali, Kazim (Poets on poetry., 2016)
Kazim Ali uses a range of subjects--the politics of checkpoints at international borders; difficulties in translation; collaborations between poets and choreographers; and connections between poetry and landscape, or between biotechnology and the human body--to situate the individual human body into a larger global context, with all of its political and social implications. He finds in the quality of ecstatic utterance his passport to regions where reason and logic fail and the only knowledge is instinctual, in physical existence and breath. This collection includes Ali's essays on topics such as Anne Carson's translations of Euripides; the poetry and politics of Mahmoud Darwish; Josey Foo's poetry/dance collaborations with choreographer Leah Stein; Olga Broumas' collaboration with T. Begley; Jorie Graham's complication of Kenneth Goldsmith's theories; the postmodern spirituality of the 14th century Kashmiri mystic poet Lalla; translations of Homer, Mandelstam, Sappho, and Hafez; as well as the poet Reetika Vazirani's practice of yoga.